Vers un nouvel empirisme juridique : les Études Juridiques Empiriques et le Nouveau Réalisme Juridique - Mark C. Suchman; Elizabeth Mertz; Yannick Ganne (Clio@Themis, 2017)
The past decade has seen a return of interest in empirical research within the U.S. legal academy, hearkening back to a similar empirical turn during the ascendancy of Legal Realism in the New Deal era. However, the current revival of legal empiricism has emerged against the backdrop of several well-established traditions of empirical sociolegal research in the interdisciplinary law-and-society movement and in the social science disciplines. This article examines two of the most prominent manifestations of the “new” legal empiricism, empirical legal studies (ELS) and new legal realism (NLR), and it situates them within the preexisting sociolegal terrain. The analysis concludes by considering possible futures for empirical research on law.